Does human presynaptic striatal dopamine function predict social conformity?. (March 2014) - Stokes, Paul RA; Benecke, Aaf; Puraite, Julita; Bloomfield, Michael AP; Shotbolt, Paul; Reeves, Suzanne J; Lingford-Hughes, Anne R; Howes, Oliver; Egerton, Alice
Socially desirable responding (SDR) is a personality trait which reflects either a tendency to present oneself in an overly positive manner to others, consistent with social conformity (impression management (IM)), or the tendency to view one's own behaviour in an overly positive light (self-deceptive enhancement (SDE)). Neurochemical imaging studies report an inverse relationship between SDR and dorsal striatal dopamine D2/3 receptor availability. This may reflect an association between SDR and D2/3 receptor expression, synaptic dopamine levels or a combination of the two. In this study, we used a [ 18 F]-DOPA positron emission tomography (PET) image database to investigate whether SDR is associated with presynaptic dopamine function. Striatal [ 18 F]-DOPA uptake, (k i cer, min-1), was determined in two independent healthy participant cohorts ( n =27 and 19), by Patlak analysis using a cerebellar reference region. SDR was assessed using the revised Eysenck Personality Questionnaire (EPQ-R) Lie scale, and IM and SDE were measured using the Paulhus Deception Scales. No significant associations were detected between Lie, SDE or IM scores and striatal [ 18 F]-DOPAk i cer . These results indicate that presynaptic striatal dopamine function is not associated with social conformity and suggests that social conformity may be associated with striatal D2/3 receptor expression rather than with synaptic dopamine levels.